Analisis Risiko K3 pada Bongkar Muat di Pelabuhan dengan Metode HAZOP (Hazard Analysis and Operability Study) (Studi Kasus : PT. XYZ) - Eli Basrul Intan Purwanto; Dharma Widada; Willy Tambunan (JOURNAL OF INDUSTRIAL AND MANUFACTURE ENGINEERING, 2023)
Occupational Safety and Health (OHS) is one of the very important factors in the smooth production process so that the OHS program must be implemented in every company. One possible cause of accidents is still ignoring the requirements and regulations in OHS. Lack of awareness and concern for OHS, resulting in the risk of accidents occurring in the loading and unloading process such as blisters on the hands, slipping, and falling objects. In this case the Occupational Safety and Health (OHS) management is required to be implemented during the loading and unloading process because this is also part of the planning and control of the loading and unloading process. To analyze the hazards to OHS risk in this study, the HAZOP (Hazard Analysis and Operability Study) method aims to identify, provide assessments and overcome OHS risk factors. In the process of loading and unloading. Based on the assessment on the Risk Matrix, there are 3 (three) levels of risk levels that have the potential to cause work hazards. The level of risk consists of high risk, medium risk, low risk. From this research there are no sources of hazard that are of extreme value, 2 (two) hazard sources that have a "high risk" value are in "placing a crane, and loading and unloading, 4 (four) hazard sources that have a" moderate risk "value on "Preparing loading and unloading equipment, Installing slings and Hooks to crane cranes, Workers entering barges, and Directing transport trucks" and 1 (one) source of hazard which has a "low risk" value found in "Installing slings and hooks on hook cranes.